2012
DOI: 10.1039/c2ob26131f
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and immunochemical evaluation of a non-methylated disaccharide analogue of the anthrax tetrasaccharide

Abstract: Anthrax tetrasaccharide is an oligosaccharide expressed at the outermost surface of the Bacillus anthracis spores, featuring three rhamnoses and a rare sugar called anthrose. This motif has now been identified as a plausible component of future human vaccines against anthrax. We report herein the synthesis of a 2-O-demethylated-β-D-anthropyranosyl-(1→3)-α-L-rhamnopyranose disaccharide analogue of this tetrasaccharide from a cyclic sulfate intermediate. This disaccharide conjugated to BSA induces an anti-native… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…This study also showed that disaccharide neoglycoconjugates generated using thiol‐maleimide conjugation with a carbohydrate‐to‐protein ratio of 6 had similar antibody titres when compared to disaccharide neoglycoconjugate with a higher (19) carbohydrate‐to‐protein ratio …”
Section: Application and Impact Of Variables In Antibacterial Glycocsupporting
confidence: 52%
See 1 more Smart Citation
“…This study also showed that disaccharide neoglycoconjugates generated using thiol‐maleimide conjugation with a carbohydrate‐to‐protein ratio of 6 had similar antibody titres when compared to disaccharide neoglycoconjugate with a higher (19) carbohydrate‐to‐protein ratio …”
Section: Application and Impact Of Variables In Antibacterial Glycocsupporting
confidence: 52%
“…Milhomme et al. found that a disaccharide (Figure b) neoglycoconjugate consisting of 2‐hydroxy anthrose and rhamnose conjugated to the BSA carrier‐protein generated IgG antibodies that bound with the tetrasaccharides of native pathogen spores …”
Section: Application and Impact Of Variables In Antibacterial Glycocmentioning
confidence: 99%
“…Recently, a 2-O-demethylated-b-D-anthropyranosyl-(1!3)-a-L-rhamnopyranose disaccharide analog of the tetrasaccharide unit was synthesized and conjugated to BSA [83]. An antinative tetrasaccharide IgG antibody response was achieved in BALB/c mice and induced sera were shown to bind to native endospores.…”
Section: Immune Response Against the Conjugated Tetrasaccharidementioning
confidence: 99%
“…Assays conducted on monoclonal antibodies that target B. anthracis glycan (38,43,44) have established the immunodominant character of anthrose (38,45,46) potentially specific for B. anthracis spores (47). Similarly, spore surface carbohydrates have showed the potential of eliciting the anti-spore IgG antibodies in mice, which opens the possibility of inserting carbohydrate haptens in vaccine formulations (48). However, despite these successes, the usage of anthrose-specific reagents for treatment and diagnostic purposes presents several limitations, including (a) the more widespread presence of anthrose in B. cereus and B. thuringiensis groups than initially expected (49,50), (b) the identification of B. anthracis strains devoid of anthrose (51), and (c) the presence of anthrose analogues in the capsular polysaccharide of a Shewanella sp.…”
Section: Discussionmentioning
confidence: 99%